2009
DOI: 10.1038/emboj.2009.108
|View full text |Cite
|
Sign up to set email alerts
|

H3 lysine 4 di- and tri-methylation deposited by cryptic transcription attenuates promoter activation

Abstract: Set1-dependent H3K4 di-and tri-methylation (H3K4me2/3) have been associated with active transcription. Recent data indicate that the H3K4me2/3 also plays a poorly characterized RNA-dependent repressive role. Here, we show that GAL1 promoter is attenuated by the H3K4me2/3 deposited by cryptic transcription. The H3K4me2/3 delay the recruitment of RNA polymerase II (RNAPII) and TBP on GAL1 promoter. Inactivation of RNA decay components revealed the existence of the RNAPII-dependent unstable RNAs, initiating upstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
176
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(191 citation statements)
references
References 57 publications
13
176
2
Order By: Relevance
“…2B), supporting the transcriptional memory of GAL1. Previous reports showed that Set1 repressed GAL1 transcription in galactose-containing medium plus 0.5% glucose (11) or GAL1 induction from raffinose to galactose culture (21). We found that SET1 deletion had a minor effect on the induction kinetics of GAL1 from long-term glucose to galactose culture, especially within the first 3 h in galactose culture (Fig.…”
Section: Elimination Of Di-and Trimethylation Of H3k4 Greatly Increassupporting
confidence: 61%
See 1 more Smart Citation
“…2B), supporting the transcriptional memory of GAL1. Previous reports showed that Set1 repressed GAL1 transcription in galactose-containing medium plus 0.5% glucose (11) or GAL1 induction from raffinose to galactose culture (21). We found that SET1 deletion had a minor effect on the induction kinetics of GAL1 from long-term glucose to galactose culture, especially within the first 3 h in galactose culture (Fig.…”
Section: Elimination Of Di-and Trimethylation Of H3k4 Greatly Increassupporting
confidence: 61%
“…It was shown that Set1 is required for silencing of Ty1 retrotransposons GAL1 and PHO84 (6,11), subsequently found to be noncoding RNA-mediated (21, 29 -31). Recently, scientists (21,32) provided evidence that H3K4me2/3 recruits the Rpd3S complex to GAL1 as well as many other inducible genes that show cryptic transcription. In the case of PHO5, our recent study showed that H3K4 methylation recruits the Rpd3L complex, rather than the Rpd3S complex, to the PHO5 promoter and suppresses the aberrant chromatin remodeling at the PHO5 promoter (13).…”
Section: Discussionmentioning
confidence: 99%
“…103 Repression URA2 Pyrimidine biogenesis YES usDCI1. 104 Repression DCI1 Fatty acid metabolism YES GAL10 lncRNA 47,48,105 Repression GAL genes Galactose metabolism YES GAL10/GAL10s lncRNAs. 52,53 Promotes induction GAL genes Galactose metabolism YES KCS1 lncRNAs 106 Translational interference KCS1 Inositol hexa/hepta bisphosphate kinase YES SUT719 30,35 Repression SUR7 Plasma membrane protein YES CDC28 AS RNA 29 Promotes induction CDC28 Cell cycle regulator NO RTL.…”
mentioning
confidence: 99%
“…Additional genomic elements have been discovered that are able to regulate transcription of nearby genes through the generation of noncoding RNAs (e.g., see Hongay et al 2006;Houseley et al 2008;Pinskaya et al 2009;Gelfand et al 2011;van Werven et al 2012;Castelnuovo et al 2013), and, based on the finding that noncoding RNA synthesis appears to be a widespread phenomenon in budding yeast (David et al 2006;Neil et al 2009;Xu et al 2009), many more such regulatory examples are likely to be identified in the future.…”
Section: S Cerevisiae Genome Organizationmentioning
confidence: 99%